1982
DOI: 10.1038/300762a0
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the T24 bladder carcinoma transforming gene is linked to a single amino acid change

Abstract: Several different transforming genes have been observed in the DNA of a variety of tumours and tumour cell lines of human and rodent origin by the ability of these genes to induce morphological transformation in NIH 3T3 cells1-5. The transforming gene found in a human bladder carcinoma cell line, T24, is H-ras-1, the human homologue of the Harvey sarcoma virus oncogene (v-H-ras)6-9. In the present study we have compared the H-ras-1 genes cloned from T24 and normal human DNA. The H-ras-1 gene cloned from T24 DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
318
0
6

Year Published

1984
1984
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 668 publications
(332 citation statements)
references
References 26 publications
8
318
0
6
Order By: Relevance
“…As with the glioma cells, RasV12 expression induced cellular degeneration accompanied by cytoplasmic vacuoles in the gastric cancer cell lines (Figure 1a). However, interestingly, a transient RasV12 expression did not induce such cellular degeneration in T24, a human bladder cancer cell line known to harbor an oncogenic H-ras allele (Taparowsky et al, 1982), although the expression level of RasV12 protein was comparable to that in the cell lines mentioned above (not shown). The ability of T24 to resist RasV12-induced cellular a b Figure 1 (a) The transient transfection of oncogenic ras(V12) gene induces cytoplasmic vacuolization and cellular degeneration in the glioblastoma cell lines U251, U343 and in the gastric cancer cell lines MKN-1, TMK-1.…”
Section: Killing Of Human Cancer Cells By Oncogenic Ras Gene Expressionmentioning
confidence: 89%
“…As with the glioma cells, RasV12 expression induced cellular degeneration accompanied by cytoplasmic vacuoles in the gastric cancer cell lines (Figure 1a). However, interestingly, a transient RasV12 expression did not induce such cellular degeneration in T24, a human bladder cancer cell line known to harbor an oncogenic H-ras allele (Taparowsky et al, 1982), although the expression level of RasV12 protein was comparable to that in the cell lines mentioned above (not shown). The ability of T24 to resist RasV12-induced cellular a b Figure 1 (a) The transient transfection of oncogenic ras(V12) gene induces cytoplasmic vacuolization and cellular degeneration in the glioblastoma cell lines U251, U343 and in the gastric cancer cell lines MKN-1, TMK-1.…”
Section: Killing Of Human Cancer Cells By Oncogenic Ras Gene Expressionmentioning
confidence: 89%
“…The single base change at position 35, in the c-ras' gene recovered by transfection of DNA from the T24 human bladder carcinoma line into NIH 3T3 cells provides the first direct evidence of the involvement of point mutation in human neoplasia (Reddy et al, 1982;Tabin et al, 1982;Taparowsky et al, 1982). The guanosine to thymidine mutation which changes amino acid 12 from glycine to valine confers on the gene product transforming properties not possessed by the unaltered gene product.…”
Section: Genetic Change In the Cancer Cellmentioning
confidence: 98%
“…Coding sequence mutations, causing amino acid substitutions at critical positions within the p21 product, as well as truncation of a putative 5' exon, have been reported to represent critical steps in the Ha-ras activation process [2][3][4][5][6]. Recent microinjection experiments have also demonstrated that overdosage of the normal Ha-ras product may be sufficient to induce cell transformation [7] and, with respect to norma1 tissues, increased amounts of p21 have been found in tumor cells of primary breast carcinomas and have been shown to correlate with other clinica1 and prognostic variables [8, 91. These circumstances, and others as well, greatly support the hypothesis of an involvement of the Ha-ras proto-oncogene in tumorigenesis, although its precise role in this process still remains to be defined [lo].…”
Section: Introductionmentioning
confidence: 99%